Theoretical and Experimental Approaches to Dark Energy and the Cosmological Constant Problem - Borzou, Ahmad (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis represents a unique mix of theoretical work discussing the Lorentz theory of gravity and experimental work searching for supersymmetry with the Compact Muon Solenoid experiment at the Large Hadron Collider. It begins by reviewing a set of widely-discussed theoretical solutions to the cosmological constant problem, including a natural solution provided by the recently developed Lorentz gauge theory of gravity. The Schwartzschild metric, de Sitter space, and quantum versions of the theory are also discussed. The thesis then looks to supersymmetry for an alternative solution. The idea behind supersymmetry is reviewed and an experimental search for supersymmetry is presented. A major contribution was to estimate one of the most significant backgrounds in this search, which arises from top-antitop quark pair production or W boson production in association with multiple jets where the W boson decays into the hadronically-decaying tau leptons and neutrinos. This background was estimated through a novel method involving kinematically analogous events but including a well-measured muon. This search significantly extends limits on supersymmetric partners of gluons from previous searches.